2018
DOI: 10.1371/journal.pone.0198835
|View full text |Cite
|
Sign up to set email alerts
|

Are Mechanical Turk worker samples representative of health status and health behaviors in the U.S.?

Abstract: IntroductionAmazon’s Mechanical Turk (MTurk) is frequently used to administer health-related surveys and experiments at a low cost, but little is known about its representativeness with regards to health status and behaviors.MethodsA cross-sectional survey comprised of questions from the nationally-representative 2014 Behavioral Risk Factor Surveillance System (BRFSS) and 2014 National Health and Nutrition Examination Survey (NHANES) was administered to 591 MTurk workers and 393 masters in 2016. Health status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
126
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(156 citation statements)
references
References 27 publications
10
126
5
Order By: Relevance
“…While participants recruited from MTURK tend to be younger than most individuals requiring coronary angiography or PCI, our study did not find any major differences in attribute preferences between those <50‐years old and those >50‐years old. Our participants were also healthier than the typical patient requiring a coronary artery procedure.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…While participants recruited from MTURK tend to be younger than most individuals requiring coronary angiography or PCI, our study did not find any major differences in attribute preferences between those <50‐years old and those >50‐years old. Our participants were also healthier than the typical patient requiring a coronary artery procedure.…”
Section: Discussioncontrasting
confidence: 64%
“…22 Furthermore, recruitment through MTURK can be inexpensive compared with other methods such as organizing focus groups or paying individuals to participate in lab studies. 22 While participants recruited from MTURK tend to be younger than most individuals requiring coronary angiography or PCI, 23 our study did not find any major differences in attribute preferences between those <50-years old and those >50-years old. Our participants were also healthier than the typical patient requiring a coronary artery procedure.…”
Section: Discussioncontrasting
confidence: 54%
“…One study suggested that the health of Turkers is not representative of the population health of the United States (Walters et al, ). Though that study (i.e., Walters et al, ) mostly consisted of unidimensional indicators of physical health (i.e., influenza vaccination, smoking, physical activity, and asthma) and one unidimensional indicator of mental health (i.e., depression). Second, the present study relied solely on self‐report and cross‐sectional data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MTurk can be used to access populations that are not traditionally represented in research because of the difficulty in accessing them (Smith, Sabat, Martinez, Weaver, & Xu, ). For example, Turkers (i.e., MTurk participants) are less likely to have health insurance than a nationally representative sample (Walters, Christakis, & Wright, ). The inclusion criteria for the present study were: (a) being uninsured or underinsured, (b) having at least one chronic health condition, (c) residing in the United States, (d) being 18 years of age or older, (e) being able to read in English, and (f) having access to the internet.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, we did not include male‐oriented measures of body image (e.g., drive for muscularity) that would provide a better understanding of how weight bias influences eating/weight‐related psychopathology in men. An additional limitation is the use of a self‐selected sample from Mechanical Turk; although they are more diverse than college samples, these self‐selected samples still tend to be younger and more educated than national samples . It is also unclear whether individuals with obesity in this study had internalized the weight‐biased attitudes they endorsed.…”
Section: Discussionmentioning
confidence: 95%